Análise criminológica da subcultura delinquencial em Foz do Iguaçu: para além da fronteira entre o crime e a repressão - Abreu, Marcos Araguari de (2015)
The purpose of this research is to analyze, from the stand point of criminology, the sociocultural and criminal characteristics from the tripoint of Brazil, Paraguay and Argentina more precisely, Foz do Iguaçu, state of Paraná. This study is developed with the aid of criminology matrices according to the theory of delinquent subculture, which Albert Kircidel Cohen created from observing juvenile delinquency in the United States of America during 1950 and 1960, and through the concept of criminal subjection, introduced by Michel Misse, sociologist and lecturer at Federal University of Rio de Janeiro. Firstly, the research introduced numerical aspects and reasoning about violence at the tripoint, followed by the theoretical matrices of delinquent subculture are explored, referring to the creation of labor and psychosocial logic exclusive to Foz do Iguaçu s tripoint. Part of the analysis amplifies a series of violence incidents homicide in the north region of the city, more specifically the neighborhood of Porto Belo, identifying the dynamics and sociological and criminal perceptions that worship illegality and smuggling as driving forces of local reality. Finally, social discourse are investigated, among which the media and how they absorb a reproduce labor and psychosocial logics with the aid of carnavalization from the studies of the Russian philosopher Mikhail Mikhailovich Bakhtin and feedback or subcultural continuity. To conclude, the prospects of specific concepts of the tripoint socio-cultural reality are used to create potential criminology matrices of a delinquent subculture theory for frontiers with self-criticism, moreover, the role of state agents.